2017
DOI: 10.1007/s00296-017-3788-0
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis as an extraarticular manifestation of ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) affects sacroiliac and axial joints as well as extraarticular organs, such as the eye, lung, bowel, and heart. Although examples of renal involvement in AS, such as IgA nephropathy, amyloidosis, and glomerulonephritis, have been reported, it has not been emphasized that urolithiasis is frequently formed in the clinical course of AS. Growing evidence indicates that urolithiasis may be observed in AS patients and is more frequent than other extraarticular features. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Eliah et al 13 claimed that limited spinal mobility and pyelo-pelvic position in AS patients might be an underlying predisposing factor for urolithiasis. Korkmaz et al 14 suggested that one of the mechanisms responsible for the development of urolithiasis in AS may be intestinal inflammation as a result of enteric hyperoxaluria. Bone turnover and bone resorption activated by inflammatory cytokines can also cause hypercalciuria.…”
Section: Discussionmentioning
confidence: 99%
“…Eliah et al 13 claimed that limited spinal mobility and pyelo-pelvic position in AS patients might be an underlying predisposing factor for urolithiasis. Korkmaz et al 14 suggested that one of the mechanisms responsible for the development of urolithiasis in AS may be intestinal inflammation as a result of enteric hyperoxaluria. Bone turnover and bone resorption activated by inflammatory cytokines can also cause hypercalciuria.…”
Section: Discussionmentioning
confidence: 99%
“…21 Ankylosing spondylitis (AS), which is the most common type of spondyloarthritis (SpA), is a chronic inflammatory disease that affects the axial and sacroiliac joints. 22 AS often affects extraarticular organs such as the eyes, lungs, bowels, and heart, and urolithiasis is frequently observed in this disease. 22 A study showed that patients with SpA had a higher incidence of kidney stones than those with RA, and it was speculated that SpA was an independent risk factor for nephrolithiasis.…”
Section: Ta B L E 4 Demographic and Clinical Characteristics Of Patie...mentioning
confidence: 99%
“…Korkmaz et al summarized the previous research on the incidence rate of urolithiasis in patients with AS from 1972 to 2015 and found that the rate ranged from 1.6% to 29.11% with 0.7% to 12.5% in general population. They eventually concluded that urolithiasis was an extra-articular manifestation of AS (2).…”
Section: Introductionmentioning
confidence: 99%